Adherence to surveillance guidelines after removal of colorectal adenomas: A large, community-based study - van Heijningen, E.; Lansdorp-Vogelaar, Iris; Steyerberg, E.; Goede, S.; Dekker, E.; Lesterhuis, W.; ter Borg, F.; Vecht, J.; Spoelstra, P.; Engels, L.; Bolwerk, C.; Timmer, R.; et al. (2015)
Objective: To determine adherence to recommended surveillance intervals in clinical practice. Design: 2997 successive patients with a first adenoma diagnosis (57% male, mean age 59 years) from 10 hospitals, who underwent colonoscopy between 1998 and 2002, were identified via Pathologisch Anatomisch Landelijk Geautomatiseerd Archief: Dutch Pathology Registry. Their medical records were reviewed until 1 December 2008. Time to and findings at first surveillance colonoscopy were assessed. A surveillance colonoscopy occurring within ±3 months of a 1-year recommended interval and ±6 months of a recommended interval of 2 years or longer was considered appropriate. The analysis was stratified by period per change in guideline (before 2002: 2-3 years for patients with 1 adenoma, annually otherwise; in 2002: 6 years for 1-2 adenomas, 3 years otherwise). We also assessed differences in adenoma and colorectal cancer recurrence rates by surveillance timing. Results: Surveillance was inappropriate in 76% and 89% of patients diagnosed before 2002 and in 2002, respectively. Patients eligible under the pre-2002 guideline mainly received surveillance too late or were absent (57% of cases). For patients eligible under the 2002 guideline surveillance occurred mainly too early (48%). The rate of advanced neoplasia at surveillance was higher in patients with delayed surveillance compared with those with too early or appropriate timed surveillance (8% vs 4-5%, <0.01). Conclusions: There is much room for improving surveillance practice. Less than 25% of patients with adenoma receive appropriate surveillance. Such practice seriously hampers the effectiveness and efficiency of surveillance, as too early surveillance poses a considerable burden on available resources while delayed surveillance is associated with an increased rate of advanced adenoma and especially colorectal cancer.